Modeling cartilage pathology in mucopolysaccharidosis VI using iPSCs reveals early dysregulation of chondrogenic and metabolic gene expression - Broeders, M.; van Rooij, Jgj; Oussoren, E.; van Gestel, Tjm; Smith, Ca; Kimber, Sj; Verdijk, Rm; Wagenmakers, Maem; van den Hout, Jmp; van der Ploeg, At; Narcisi, R.; Pijnappel, Wwmp (Frontiers in Bioengineering and Biotechnology, 2022)
Mucopolysaccharidosis type VI (MPS VI) is a metabolic disorder caused by disease-associated variants in the Arylsulfatase B (ARSB) gene, resulting in ARSB enzyme deficiency, lysosomal glycosaminoglycan accumulation, and cartilage and bone pathology. The molecular response to MPS VI that results in cartilage pathology in human patients is largely unknown. Here, we generated a disease model to study the early stages of cartilage pathology in MPS VI. We generated iPSCs from four patients and isogenic controls by inserting the ARSB cDNA in the AAVS1 safe harbor locus using CRISPR/Cas9. Using an optimized chondrogenic differentiation protocol, we found Periodic acid–Schiff positive inclusions in hiPSC-derived chondrogenic cells with MPS VI. Genome-wide mRNA expression analysis showed that hiPSC-derived chondrogenic cells with MPS VI downregulated expression of genes involved in TGF-β/BMP signalling, and upregulated expression of inhibitors of the Wnt/β-catenin signalling pathway. Expression of genes involved in apoptosis and growth was upregulated, while expression of genes involved in glycosaminoglycan metabolism was dysregulated in hiPSC-derived chondrogenic cells with MPS VI. These results suggest that human ARSB deficiency in MPS VI causes changes in the transcriptional program underlying the early stages of chondrogenic differentiation and metabolism.